John Constantine, Hellblazer. Scab - Milligan, Peter (Vertigo, 2009)
John Constantine, having sought treatment for his skin condition and experienced some relief, finds one scab will not heal and searches his past for a clue about what is causing it, uncovering facts about a dockers' strike in which he got his hands dirty.